Classifications in Facial Plastic Surgery. - Oxley, Paul J. (Paul James) (Plural Publishing, Inc., 2009)
Clearly and concisely lays out all the commonly used and rarer classification systems for facial plastic surgery, with explanations as to their use. Coverage includes the staging of oral and cutaneous cancers, types of cleft lips and palates, and severity of facial injuries, among others. All of the major fields within facial plastic surgery are incorporated and, within each, up to 30 classifications are included.